DEVELOPMENT OF SELF-DISCIPLINE OF STUDENTS THROUGH SCOUT ACTIVITIES, WAT PHRA MAHATHAT SCHOOL, UNDER THE OFFICE OF THE PRIMARY EDUCATION AREA, NAKHON SI THAMMARAT, AREA 1 - Phetchchana , Krittiyaphon; PhrakhruSumetpariyatkhun; Srisuwan, Kasama (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) study the self-discipline of students at Wat Phra Mahathat School, 2) study the ways to develop students' self-discipline through scout activities at Wat Phra Mahathat School under the Nakhon Si Thammarat Primary Educational Service Area Office 1, and 3) presenting guidelines for developing self-discipline in students through scout activities at Wat Phra Mahathat School, under the Office of the Primary Education Nakhon Si Thammarat Area 1. It is a qualitative research by conducting in-depth interviews with 15 stakeholders, in-depth interviews with 5 experts, and focus group discussions with 7 experts. The research tools were interview forms and focus group discussions. Data were analyzed using content analysis. The research results found that: 1) the self-discipline of students at Wat Phra Mahathat School focused on important characteristics, including patience, responsibility, determination, self-confidence, leadership, determination, and honesty. Problems found: The school had more students than the area could accommodate, causing overcrowding. Teachers were not able to provide adequate care, making it difficult to control student behavior. Social media was not moderated, causing children to imitate inappropriate behavior. 2) Guidelines for developing self-discipline in students through scout activities at Wat Phra Mahathat School included: 1) Patience, 2) Responsibility, 3) Determination, 4) Self-confidence, 5) Leadership, 6) Determination, and 7) Honesty by integrating with scouting activities, the implementation steps included planning, implementation, monitoring and development and improvement. 3) The presentation of the guidelines for developing self-discipline in students through the scout activities of Wat Phra Mahathat School as all experts in the focus group agreed that it was appropriate, feasible, and beneficial for use in developing self-discipline in students.